Ethnic Polarization, Potential Conflict, and Civil Wars - Montalvo, José G; Reynal-Querol, Marta (American Economic Review, 2005)
The increasing incidence of ethnic conflicts, and the much-publicized consequences of these conflicts, have attracted the interest of many researchers in the social sciences. Many studies have addressed directly the issue of ethnic diversity and its effects on social conflicts and civil wars. Political scientists have stressed the importance of institutions in the attenuation or intensification of social conflict in ethnically divided societies. Recently economists have connected ethnic diversity with important economic phenomena like investment, growth, or the quality of government (William Easterly and Ross Levine, 1997; Alberto Alesina et al., 2003; Rafael La Porta et al., 1999). The number of papers dealing with the effects of ethnic diversity on issues of economic interest is growing rapidly. In this respect, it is common in recent work to include as a regressor in empirical growth estimations an index of ethnic fractionalization. There are several reasons to include such an indicator. First, some authors have argued that ethnically diverse societies have a higher probability of ethnic conflicts, which may lead to civil war. The political instability caused by potential ethnic conflicts has a negative impact on investment and, indirectly, on growth. Second, ethnic diversity may generate a high level of corruption which, in turn, could deter investment. Finally it has been argued that in heterogeneous societies the diffusion of technological innovations is more difficult, especially when there is ethnic conflict among groups in a country. Business as usual is not possible in a society with a high level of potential ethnic conflict, since this situation affects all levels of economic activity. Trade may be restricted to individuals of the same ethnic group; public infrastructure may have an ethnic bias; government expenditure may favor some ethnic groups, etc. The common element in all these mechanisms is the existence of an ethnic conflict which, through social and political channels, spreads to the economy. However, many empirical studies find no relationship between ethnic fractionalization, ethnic conflict, and civil wars. There are at least three alternative explanations for this. First, it could be the case that the classification of ethnic groups in the Atlas Nadorov Mira (henceforth ANM), source of the traditional index of ethnolinguistic fractionalization (ELF), is not properly constructed. Some authors have used other sources to construct datasets of ethnic groups for a large sample of countries. In general, the correlation between the index of fractionalization obtained using these alternative data sources is very high (over 0.8). Second, James D. Fearon (2003) has argued that it is important to measure the “ethnic distance” across groups in order to obtain indicators of cultural diversity. He measures these distances in terms of the proximity in a tree diagram of the families of languages of different countries. As in the case of alternative data sources, the correlation of the index of ethnic fractionalization, using these distances, with the original ELF index is very high, 0.82. * Montalvo: Department of Economics, Universitat Pompeu Fabra, C/Ramon Trias Fargas 25-27, Barcelona 08005 Spain, and Instituto Valenciano de Investigaciones Economicas (e-mail: montalvo@upf.es); Reynal-Querol: the World Bank, 1818 H Street, NW, Washington, DC 20433 (e-mail: mreynalquerol@worldbank.org). We are grateful for comments by Antonio Villar, Joan Esteban, Paul Collier, Tim Besley, and two anonymous referees. We thank the participants of seminars at the World Bank, Institut de la Mediterranea, Toulouse, Brown University, the European Economic Association Meetings, and the Winter Meetings of the Econometric Society. We would like to thank Sergio Kurlat, William Easterly, and Anke Hoeffler for sharing their data. Financial support from the BBVA Foundation and the Spanish Secretary of Science and Technology (SEC2003-04429) is kindly acknowledged. Jose G. Montalvo thanks the Public Services Group of the Research Department (DECRG) of the World Bank, where most of the revision of this paper was done, for their hospitality. The conclusions of this paper are not intended to represent the views of the World Bank, its executive directors, or the countries they represent. 1 Measured by the ELF index using the data of the Atlas Nadorov Mira. 2 Montalvo and Reynal-Querol (2000), Alesina et al. (2003), or Fearon (2003). 3 See also Francesco Caselli and W. John Coleman (2002).